2024
DOI: 10.1098/rsta.2023.0197
|View full text |Cite
|
Sign up to set email alerts
|

Transport of dust across the Solar System: Constraints on the spatial origin of individual micrometeorites from cosmic-ray exposure

J. Feige,
A. Airo,
D. Berger
et al.

Abstract: The origin of micrometeorites (MMs) from asteroids and comets is well-established, but the relative contribution from these two classes remains poorly resolved. Likewise, determining the precise origin of individual MMs is an open challenge. Here, cosmic-ray exposure ages are used to resolve the spatial origins of 12 MMs collected from urban areas and Antarctica. Their 26 Al and 10 Be concentration, produced during cosmic-ray irradiation in space, were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(213 reference statements)
0
1
0
Order By: Relevance
“…The first two papers focus on the detection and analysis of meteors and meteorites. The opening paper by Feige et al [18] investigates the precise origins of 12 MMs to constrain whether MMs found in urban areas or Antarctica originated from comets or asteroids. This study measures concentrations of aluminium-26 and beryllium-10 via mass spectrometry and compares the results with a model concerning the transport and irradiation of precursors of these meteorites in space.…”
mentioning
confidence: 99%
“…The first two papers focus on the detection and analysis of meteors and meteorites. The opening paper by Feige et al [18] investigates the precise origins of 12 MMs to constrain whether MMs found in urban areas or Antarctica originated from comets or asteroids. This study measures concentrations of aluminium-26 and beryllium-10 via mass spectrometry and compares the results with a model concerning the transport and irradiation of precursors of these meteorites in space.…”
mentioning
confidence: 99%